Comparative Analysis of Indonesian Language Learning Outcomes through PowerPoint and Picture Media on Fourth-Grade Students’ Writing Ability - Hafsah Nasution, Siti; Rahmat Kartolo; Sutikno (PT Inovasi Pratama Internasional, 2026)
This study aims to analyze the comparative results of Indonesian language learning through the use of PowerPoint and picture media on the writing ability of fourth grade students of State Elementary School 112 Parbangunan, Mandailing Natal Regency in the 2025–2026 Academic Year. The background of this study is the low writing ability of students due to the lack of variety of learning media used. Writing is a basic skill in learning Indonesian that needs to be developed early on because it is closely related to the ability to think, organize ideas, and communicate thoughts in writing. This study uses a comparative quantitative approach with a Nonequivalent Control Group Design. The population of the study was all 40 fourth-grade students of SD Negeri 112 Parbangunan, divided into two groups: class IVA as the experimental group with PowerPoint media and class IVB as the control group with image media. The research instrument was a writing test given during the pretest and posttest. The data analysis technique used a normality test, homogeneity test, and t-test to determine significant differences between the two groups. The results showed that the average posttest score of students who learned with PowerPoint media was higher than students who used image media. Based on the t-test, the t-count value was 2.27 with a t-table of 2.024 at a significance level of 0.05. Because t-count> t-table, there is a significant difference between the two media. Thus, it can be concluded that PowerPoint media is more effective than image media in improving students' writing skills